Comparing PBMC isolation approaches and assessing epigenetic immune cell quantification as quality control for PBMCs - Lukas Heller; Isabell Janack; Konstantin Schildknecht; Udo Baron; Sven Olek (PLoS ONE, 2026)
Ex vivo stability of whole blood is limited. To conserve the mononuclear cell fraction, PBMCs are isolated, stored and serve as substrate for downstream analyses. The quality of PBMCs depends on the purification procedure. Thereby, anti-coagulants, collection tubes, storage temperature and time before isolation, as well as the separation matrix and protocols during purification may impact quality of the resulting PBMC product. However, only a limited number of key quality indicators (KPIs) are currently used to characterize PBMC isolates focusing on viability and overall cell count. Here, the effect of the relevant purification parameters on those KPIs was assessed, and epigenetic immune cell analysis was introduced to provide an additional performance indicator. This method was also compared to flow cytometric analysis, currently the gold standard tool for immune cell quantification. Sample quality differed significantly depending on tube type/anticoagulant, pre-purification temperature and times. The choice of the purification procedure, including the separation matrix, had a minor effect and freshly processed blood yielded good processing results independent of the protocol. Unsurprisingly, the loss of sample integrity that occurred prior to purification cannot be rescued by downstream isolation protocols. The longer the time from blood draw to PBMC purification, the more granulocyte contamination was observed impairing PBMC purity. With given tubes and temperatures, PBMC quality is chiefly dependent on time-to-process, arguably the parameter most difficult to control in sample logistics and clinical trials. The often-used key performance indicators focusing only on cell viability and recovery are of limited value, as they may be falsified by potential granulocyte contamination. Thus, as additional quality parameter, we propose ”true recovery”, i.e., recovery of lymphocytes and monocytes only. These subfractions can be measured easily by qPCR-based epigenetic immune cell counting. Such an approach may provide better comparability across sample analyses in clinical trials.